Demographic and histopathologic features of dogs with abnormally high concentrations of hepatic copper. (1st November 2022) - Ullal, Tarini Vedantham; Lakin, Steven; Gallagher, Brooke; Sbardellati, Nick; Abdo, Zaid; Twedt, David C.
Abstract: Background: Copper associated hepatopathy (CAH) has become an important and prevalent disease since the 1990's, coincidental with changes in copper (Cu) content in commercial dog foods. Knowing the demographic and histopathologic features related to hepatic Cu concentrations might aid in diagnosing CAH in dogs. Hypothesis/Objectives: The primary aim was to identify demographic and histopathologic features associated with abnormally high hepatic Cu concentrations. Animals: Dogs that underwent liver histopathology and Cu quantification at a veterinary diagnostic laboratory between July 2010 and February 2020. Methods: Data was retrospectively collected from an electronic database. A Gaussian multiple regression model on the log scale was used to evaluate associations between hepatic Cu and a set of demographic and histologic features selected with machine learning methods. Results: Of 4559 cases meeting criteria, 50% had hepatic Cu > 400 and 19% had Cu > 1000 ppm (parts per million) dry weight (reference range 120‐400). Median hepatic Cu was 391 ppm, range 4.5 to 31500. Age was negatively associated ( P < .02), but specific breeds (Doberman pinscher, Labrador retriever, and West Highland white terrier) were positively associated with abnormally high hepatic Cu ( P < .001). Severity of inflammation (mild, moderate, and severe) and necrosis/apoptosis were associated with abnormally high hepatic Cu ( P < .01). Conclusion and Clinical Importance: Abnormally high hepatic Cu is prevalent in hepatic biopsies from dogs. Machine learning modeling showed that necroinflammation, not cholestasis or cirrhosis, on hepatic histopathology, is predictive of higher hepatic Cu and might be a reliable histologic predictor of CAH.